EVALUASI PROGRAM EKSTRAKURIKULER DI SDN CANDIREJO KABUPATEN SEMARANG - Damayanti, Winny Rosa; Dwikurnaningsih, Yari (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
The purpose of this research was to evaluate about context, input, process, and product of extracurricular program in SDN Candirejo Kabupaten Semarang. This type of research was evaluation research by CIPP model. This research method used descriptive qualitative method. This research fosused on extracurricular program in SDN Candirejo Kabupaten Semarang. Data collection techniques used interview, observation and documentation study. Data validity techniques  used tringulation of technique and source. Data analysis steps were data collection, data reduction, data display and data verification. The result of this research were (1) The context aspects was in accordance with Extracurricular Technical Guide in Elementary School, such as extracurricular program background was to facilitate and develop student’s potential, talents and interests, and to cultivate student’s mentally and self-confidence. (2) Input aspects included planning, human resource involved, and financing were adequate and in accordance with Extracurricular Technical Guide in Elementary School. Extracurricular facilities need to be improved; (3) Process aspects were extracurricular program implementation included program mechanism, program implementation, facilities management, human resource and financing were in accordance with program planning that has been prepared which reffering to Extracurricular Technical Guide in Elementary School. (4) Product aspects were increased student’s skill, the school often got requests to perform at events, received more than 35 students every year; (5) supporting factors such as team work, commitment and competent human resource. Inhibiting factors such as limited partners, extracurricular class was not yet available.